2015
DOI: 10.1002/isaf.1381
|View full text |Cite
|
Sign up to set email alerts
|

Private‐Value Auction Versus Posted‐Price Selling: An Agent‐Based Model Approach

Abstract: SUMMARYAn agent-based first-price private-value auction and an agent-based posted-price market are developed to compare these selling methods when buyers have private values. If the seller cannot impose a reserve price and has little uncertainty about the item's value, the seller's expected revenue is highest in the posted-price market. Otherwise, the seller is better off selling the item with the auction. Using a genetic algorithm and Monte Carlo integration solved the agent-based models quicker and provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…In this experiment, the monthly wholesale prices from 2013 were used as the estimated prices of 2014. Same with previous researches (Hamm et al 2007;Boyer et al 2015), we used random rotation schedules as the start for the simulation in our paper. The optimization was performed 100 simulation periods and each virtual farmer adjusted the rotation schedule based on the profit-experience of the previous simulations until the optimal schedule was determined (Fig.…”
Section: Experiments I: Optimization Without Self-adaptationmentioning
confidence: 99%
“…In this experiment, the monthly wholesale prices from 2013 were used as the estimated prices of 2014. Same with previous researches (Hamm et al 2007;Boyer et al 2015), we used random rotation schedules as the start for the simulation in our paper. The optimization was performed 100 simulation periods and each virtual farmer adjusted the rotation schedule based on the profit-experience of the previous simulations until the optimal schedule was determined (Fig.…”
Section: Experiments I: Optimization Without Self-adaptationmentioning
confidence: 99%
“…ABM is also widely employed to study qualitative variables that are not directly observed and/or difficult to measure empirically. For example, Kawakubo, Kiyoshi, and Shinobu () propose an artificial market model for derivatives, Li and Li () introduce an ABM framework for international marketing planning, and Boyer, Brorsen, and Fain () use ABM for comparing private‐value auctions and posted‐price markets. In the specific field of innovation, we could mention the agent‐based models developed in: (1) Oldham () to study industrial dynamics with innovator and imitator competitors; (2) Long and Li () to analyse intra‐ and interorganization innovation networks; and (3) Rixen and Weigand () to evaluate different policies for the diffusion of an innovation.…”
Section: Introductionmentioning
confidence: 99%